The Influence of Social Capital on Social Mobilityof the Middle Class Society - Nuriyah Hanik Fatikhah (Socious Journal, 2026)
Social capital encompassing trust, social networks, and cooperative norms is widely recognized as a crucial yet unevenly distributed resource that shapes individuals' capacity for upward social mobility. This study investigates how different dimensions of social capital, specifically bonding, bridging, and linking capital, influence the social mobility trajectories of the middle class in contemporary society. Drawing on a systematic literature review and synthesis of quantitative and qualitative empirical evidence from diverse national contexts, including Indonesia, the United States, Brazil, Kenya, and Chile, this research maps the mechanisms through which social capital facilitates or constrains middle-class advancement. Three analytical pathways are identified: network-based opportunity access, educational capital conversion, and institutional trust as a mobility enabler. Findings reveal that bridging social capital cross-class heterogeneous networks demonstrates the strongest association with upward mobility, while bonding capital primarily serves stabilizing and resilience functions. Linking capital, representing access to institutional power, is shown to be critical but highly unequally distributed. This study contributes novelty by synthesizing multi-country evidence within a unified three-dimensional social capital framework, offering policy implications for expanding social capital access among aspiring middle-class populations.